Event-Related Potentials Reveal Altered Executive Control Activity in Healthy Elderly With Subjective Memory Complaints - Cespón, Jesús; Galdo-Álvarez, Santiago; Díaz, Fernando (Frontiers in Human Neuroscience, 2018)
Several studies reported that healthy elderly with subjective memory complaints evolve to Alzheimer’s disease more frequently than elderly without subjective memory decline. In the present study, we investigated event-related potentials associated to executive control processes taking place during the performance of a Simon task with two irrelevant dimensions (stimulus position and direction pointed by an arrow) in healthy elderly divided in low and high subjective memory complaints (LSMC, HSMC) groups. P300 was studied as a correlate of working memory. Medial frontal negativity (MFN) was studied as a correlate of conflict monitoring. Whereas the LSMC group showed interference from the stimulus position, participants with HSMC showed interference from both irrelevant dimensions. P300 latency was longer and P300 amplitude was lower when the stimulus position was incompatible with the required response but differences between both groups were not observed. MFN was not modulated in the LSMC group; however, the HSMC group showed larger MFN when the stimulus position and/or the direction pointed by the arrow were incompatible with the required response. These results suggest that participants with high subjective memory complaints deployed greater conflict monitoring activity to maintain the performance when the target stimulus contained conflictive spatial information.